2013
DOI: 10.1017/s2040174413000226
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antenatal factors and postnatal growth on serum adiponectin levels in children

Abstract: Low levels of serum adiponectin (i.e. hypoadiponectinaemia) are a marker of cardiometabolic risk in overweight children. It is not clear whether early-life factors may play a role in the development of hypoadiponectinaemia. We investigated whether antenatal factors and postnatal growth are associated with childhood adiponectin levels. This was an observational study in a birth cohort (Vulnerable Windows Cohort Study). Anthropometry was measured at birth, at 6 weeks, every 3 months up to 2 years and then every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This finding is consistent with recently published data from our unit which demonstrated that placental size, foetal size, gestational age and newborn size were not significantly associated with serum adiponectin levels although faster growth in BMI during late infancy and childhood was associated with lower adiponectin levels. 22…”
Section: Birth Size and Adiponectinmentioning
confidence: 99%
“…This finding is consistent with recently published data from our unit which demonstrated that placental size, foetal size, gestational age and newborn size were not significantly associated with serum adiponectin levels although faster growth in BMI during late infancy and childhood was associated with lower adiponectin levels. 22…”
Section: Birth Size and Adiponectinmentioning
confidence: 99%
“…Most studies on the developmental origin of health and disease (DOHAD) have been conducted in developed countries. While there is an accumulating body of data from developing countries, including Jamaica (10,(24)(25)(26)(27)(28)(29), data from African origin populations are still limited. In the Caribbean, studies on the early life influences on blood pressure have looked mainly on the effects of intrauterine growth and blood pressure in childhood or adolescence.…”
Section: Introductionmentioning
confidence: 99%